Azide–Alkyne Cycloaddition En Route to 1H-1,2,3-Triazole-Tethered Isatin–Ferrocene, Ferrocenylmethoxy–Isatin, and Isatin–Ferrocenylchalcone Conjugates: Synthesis and Antiproliferative Evaluation - Singh, Amandeep (ACS Omega, 2018)
[Image: see text] Diverse series of isatin–ferrocene conjugates were synthesized via Cu-promoted azide–alkyne cycloaddition reaction with an aim of probing their antiproliferative structure–activity relationship against MCF-7 (estrogen receptor positive) and MDA-MB-231 (triple negative) cell lines. Among the synthesized conjugates, isatin–ferrocenes proved to be more potent against MCF-7, whereas ferrocenylmethoxy–isatins exhibited activity against MDA-MB-231 cell lines. However, the introduction of chalcone moiety among these hybrids resulted in the complete loss of activity against the tested cell lines, as evident by isatin–ferrocenylchalcones. The conjugates 5a and 9c proved to be the most potent among the series against MCF-7 and MDA-MB-213 cell lines, exhibiting IC(50) values of 31.62 and 20.26 μM, respectively.